Development of Bio-control Technology for Subterranean Termites Coptotermes curvignathus Holmgren Using Electromagnetic Waves - Farah Diba; Ferry Hadary; Seno Darmawan Panjaitan; Tsuyoshi Yoshimura (Masyarakat Peneliti Kayu Indonesia, 2010)
This paper proposes a non-destructive technology to control subterranean termites Coptotermes curvignathus Holmgren infestations. In the experiment, the apparatus for termites control used electromagnetic waves at two frequencies: 300 Hz and 300 kHz. Termites were exposure to electromagnetic waves on direct methods with variation of exposure time 15, 30, 45 and 60 min respectively. The use of electromagnetic waves for termites control are very beneficial, they are odorless, noiseless, friendly to environment, and easy to apply. The result showed that electromagnetic waves had an effect to termites. The value of termites mortality was range between 25.45 82.27% and the average value of termites filter paper consumption was between 8.89 39.44%. Meanwhile on control treatment, termites mortality and termites filter paper consumption were respectively 14.05% and 79.88% in average. The highest frequency of electromagnetic waves and the longest irradiation time caused the highest average value of termites mortality. The magnitude field from apparatus was range between 0.069 0.1815 μT, which is safe to utilize around the human body. The best result was achieved on frequency 300 kHz and irradiation time 60 min. These results represent important information about the potential use of electromagnetic waves technology for termites control as an environmentally benign alternative in spite of the insecticides uses.